Interferon-gamma (IFN-γ): reviewing its mechanisms and signaling pathways on the regulation of endothelial barrier function - Ng, Chin Theng; Fong, Lai Yen; Abdullah, Muhammad Nazrul Hakim (Elsevier, 2023)
Interferon-gamma (IFN-γ) is a pleiotropic cytokine that plays a critical role in mediating an array of immune responses including promotes antiviral activity, facilitates macrophage activation, controls Th1/Th2 balance, and regulates cellular apoptosis and proliferation. A few articles have previously reviewed the effects of IFN-γ in the regulation of barrier permeability, but none of these articles focuses on barrier function of endothelial cells. This review aims to discuss the regulatory mechanisms of IFN-γ on endothelial barrier function and its underlying signaling pathways. Articles were retrieved from electronic databases such as PubMed and Google Scholar using keywords “Interferon-gamma”, “endothelial cells”, “barrier function”, and “signaling pathway”. The articles published between 2000 and 2022 that are related to the aforementioned topics were selected. A few journals published beyond this period were also included due to limited information available. The results showed that IFN-γ modulates endothelial barrier function, mainly involves small GTPases, STAT1-dependent pathway, p38 MAPK and nitric oxide. In conclusion, more in depth cellular and molecular studies are needed to elucidate the pathways of IFN-γ in the regulation of endothelial barrier function.